Topography of a dream, or some features of nonlinear narrative - Keturakis, Saulius (Creativity Studies, 2016)
The article deals with the turn of the poetry of linear narrative into three-dimensional shapes, while topography and other spatial disciplines becomes an important tool to understand the meaning of new hypertextual narrative. Relying on the metaphors of Ted Nelson, the creator of the concept of hypertext about the magical and oneiric nature of a nonlinear story, the article represents the relationships between the topography of the spiritual world of the British Romanticism, written media transformation to a three-dimensional spatial structure in Nelson’s hypertext project and postmodern practices of cultural dismantling. The article concludes that the traditional writing about hypertext is often not able to cover part of its features; the attention is drawn to the nature of hybrid art/scientific analysis of the new, intermedial “writing”.First published online: 27 Oct 2015